دراسة مقارنة لفعالية مستخلصات ثمار نباتية مختلفة على الصفات الحيوية ضمن مراحل تطور الاكاروس الأحمر ذو البقعتين Tetranychus urticae Kock ( Acari:Tetranychidae) - صقر إبراهيم; غالية سهير (Latakia University Journal -Biological Sciences Series, 2018)
This study was done to find ways that decrease the negativity of chemical pesticides which they are used for pests control . For that ,a lot of laboratory tests were done ,in Faculty of Agriculture, Tishreen University, to estimate the efficacy of six extracts of wild plant fruits in controlling the T.urticae communitie, Because these extracts are natural products that they are dissolve biologically, and they are more safety and specialty. Results of new eggs treatment showed that the effect of extracts of Melia azedarach, E. camaldulensis, L. camara , S.aspira, S.officinalis and C. sempervirens fruits lasted between 21.31 -22.95%, and exceeded 36 and 42% for S. aspira and S. officinalis respectively. The greatest effect (100%) happened after 3 days of new larve treatment with fruit extract of M.azedarach, 5 days for S. officinalis and S. aspira , and 7 days for L. camara . S.officinalis, L.camara and S.aspera extracts are showed the total effect (100%) after 5-7 days of adult female treatment, While the efficacy of M.azedarach and E.camaldulensis extracts lasted about 90% . The less effect, although good, was achieved by C.sempervirens extract. The number of eggs placed by new females decreased about 90% with M.azedarach and S.officinalis extracts , and 83% with , L.camara extract. The placed eggs ratio with all extracts didn’t exceed 42.29% which happened with C .sempervirens extract. Significant differences between all treatment and control were found and although with the three growth phases of T.urticae which tested in this study. أجريت وبهدف البحث عن سبيل للحد ما أمكن من سلبيات المبيدات الصنعية المستخدمة لمكافحة الآفات, تجارب مخبرية في كلية الزراعة, بجامعة تشرين, لتقدير كفاءة المستخلصات المائية لثمار ستة نباتات برية في السيطرة على مجتمعات الاكاروس الأحمر ذوالبقعتين urticae T., كونها تمثل مركبات طبيعية تتفكك بيولوجيا وأكثر تخصصاً وأماناً وهي ,Melia azedarach Eucalyptus camaldulensis, Styrax officinalis, Smilax aspir, Lantana camara, Cupressus sempervirens. أظهرت نتائج معاملة البيوض بقاء فعالية مستخلصات ثمار كل من الازدرخت, الكينا, الديس الإفرنجي, والسرو ما بين 21.31- 22.95 % وتجاوزت 36 و42 % مع السمالكس و الاصطرك على التوالي. تحقق التأثير الأعظمي 100% بعد 3أيام من معاملة اليرقات الحديثة بمستخلصات ثمار الازدرخت و5 أيام مع الاصطرك والسمالكس5 و 7 أيام بالديس الإفرنجي. أظهرت مستخلصات الاصطرك والديس الإفرنجي والسمالكس التأثير الكلي (100%) بعد 5 و7 أيام لمعاملة الإناث البالغة , وبقيت فعالية الازدرخت والكينا بحدود 90% و التأثير الأقل وإن كان جيدا ً أعطاه مستخلص السرو 80.32 %. تراجعت أعداد البيض التي وضعتها الإناث الحديثة قرابة 90% مع الازدرخت والاصطرك و83% مع الديس الإفرنجي , ولم تتجاوز نسبة البيض الموضوع مع كافة المستخلصات 42.29% والتي تحققت مع مستخلص السرو . وجدت فروق معنوية بين كافة المعاملات والشاهد وبالنسبة لأطوار النمو الثلاثة التي اختبرت.